2019
DOI: 10.4084/mjhid.2019.028
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation, Laboratory Analysis and Linear Growth in 50 Neonates and Young Infants With Acute Meningitis: One Year Experience of a Single Center in Qatar

Abstract: Abstract Introduction: Meningitis occurs frequently in neonates and can lead to a number of acute, severe complications and long-term disabilities. Although, long term growth delay and abnormal weight gain appear to be risk factors following an acute attack of both bacterial and aseptic meningitis in children, especially during the fast phase of infantile growth, the long-term effects of acute meningitis occurring during the neonatal and early infantile periods on linear growth (length, weight and head g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…However, the most common infection of the central nervous system is aseptic meningitis. In a study of young infants with acute meningitis, almost 80% of infants were found to have aseptic meningitis [3]. In our study, 274 patients (31.6%) were diagnosed with meningitis.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…However, the most common infection of the central nervous system is aseptic meningitis. In a study of young infants with acute meningitis, almost 80% of infants were found to have aseptic meningitis [3]. In our study, 274 patients (31.6%) were diagnosed with meningitis.…”
Section: Discussionmentioning
confidence: 49%
“…CSF pleocytosis was defined as a CSF WBC count > 22 WBCs/ mm 3 tient was between 4 and 7 weeks of age; and > 5 WBCs/mm 3 if the patient was ≥ 8 weeks old. UTI was diagnosed as a urine culture (collected by urethral catheterization) with more than 100,000 colony-forming units/mL [11].…”
Section: Laboratory Tests and Microbiological Tests Of Csf Blood Urmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal meningitis is a severe medical condition in infants that is rapidly fatal if untreated [20]. Mortality is approximately half in developing countries and ranges from 8%-12.5% in developed countries [10].…”
Section: Prognosismentioning
confidence: 99%
“…Most studies regarding neonatal meningitis focus on the microbiology, epidemiology, clinical manifestations and outcomes of GBS diseases, and fewer studies look at E. coli meningitis [3][4][5][6][7][8][11][12][13]. Little is known about the differences between GBS meningitis and Gram-negative bacillary (GNB) meningitis in neonates, although some studies have found some uncommon GNB species as the cause of neonatal meningitis [11][12][13]. The neurological sequelae and complications after GNB meningitis are supposed to be different from those caused by GBS or other Gram-positive pathogens in neonates and young infants [1,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%